Smoking, serum antioxidant vitamin levels and age-related macular degeneration - (:unkn) unknown (International Journal of Ophthalmology (c/o Editorial Office), 2014)
AIM: To evaluate associations between the grades of age related macular degeneration (AMD) and serum levels of antioxidant vitamins (vitamin A, C and E) and smoking. METHODS: Fifty-three AMD patients and 31 individuals having ages matching with the patient group were enrolled the study. Colored fundus photographs of the macula were used to place participants (n=84) into one of the five groups (Grade I-V) based on the frequency and severity of the lesions associated with AMD. Serum antioxidant vitamin levels were measured using High Performance Liquid Chromatography (HPLC). Smoking status was classified as non-smoker, ex-smoker and current smoker. Total number of packs smoked per year, was defined. RESULTS: The distribution of vitamin A, E, and C levels were 0.874±0.326 mg/L, 10.739±4.874 mg/L, 1.737±0.447 mg/L in control group and 0.880±0.305 mg/L, 9.487±6.060 mg/L, 1.870±2.191 mg/L in AMD group, respectively. The difference between AMD and control group was not statistically significant for vitamin A, E and C levels (P>0.05). There were no significant differences between subgroups of AMD for vitamin A (P=0.881) and vitamin E (P=0.293) but there was a contradicting rise of vitamin C levels (P=0.044) with increasing levels of the disease. There were no significant differences between AMD and control group regarding smoking status, but there was a significant difference for total number of packs smoked per year (P=0.02). An increase of number of total packs smoked per year was determined along with the rising grade of AMD (P=0.007). CONCLUSION: We found no relation between AMD and serum levels of vitamin A and E but vitamin C levels was increase with AMD grades unexpectedly. We found dose-response relationship between smoking and AMD.
Keywords: Age related macular degeneration; Antioxidant vitamin; Smoking